2016
DOI: 10.1007/s00436-016-5087-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Enterococcus faecalis CECT 7121 on Cryptosporidium parvum infection in mice

Abstract: Cryptosporidium is an opportunistic protozoan parasite of humans and animals worldwide and causes diarrheal disease that is typically self-limiting in immunocompetent hosts but often life threatening to immunocompromised individuals. However, there is a lack of completely efficient therapy available. Probiotics have attracted the attention as potential antiparasite compounds against protozoa involved in intestinal infections. This study investigated the effects of administration of probiotic Enterococcus faeca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 25 publications
(27 reference statements)
1
10
0
Order By: Relevance
“…This phenotype was attributed to a reduced epithelial cell turnover. The effect of probiotics on the course of cryptosporidiosis was also observed by others [22, 23]. This research uncovered a beneficial effect of Enterococcus faecalis administration to mice infected with C .…”
Section: Introductionsupporting
confidence: 80%
“…This phenotype was attributed to a reduced epithelial cell turnover. The effect of probiotics on the course of cryptosporidiosis was also observed by others [22, 23]. This research uncovered a beneficial effect of Enterococcus faecalis administration to mice infected with C .…”
Section: Introductionsupporting
confidence: 80%
“…and rotavirus are both intracellular pathogens that invade and affect the same target cells (superficial enterocytes) of the small intestine [54,55], resulting in similar lesions, it can be speculated that they occupy the same cellular or subcellular niches (i.e., receptors, signaling pathways), and/or that infection with one of them somehow interferes with the ability of the other to cause further intestinal damage and diarrhea. A study in mice experimentally infected with C. parvum and a strain of Enterococcus faecalis administered as a probiotic demonstrated that when both agents were present in the same intestinal location, the bacterium interfered with C. parvum infection [56].…”
Section: Discussionmentioning
confidence: 99%
“…The primary route of bacterial activity to parasitic hitting possibly through boosting gut hurdle (23)(24)(25)(26). Helpful bacteria could also increase useful microbiota numbering as lactobacillus, that suppress harmful bacteria development via contesting on connection region on the gut endothelial layer.…”
Section: Discussionmentioning
confidence: 99%